2020
DOI: 10.1016/j.chom.2020.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Fecal IgA Levels Are Determined by Strain-Level Differences in Bacteroides ovatus and Are Modifiable by Gut Microbiota Manipulation

Abstract: Highlights d Bacteroides ovatus strain variation drives either high or low fecal IgA d CD4 + T cells are critical in B. ovatus-mediated gut IgA production d Cocktails of IgA high B. ovatus strains convert mice from lowto high-IgA producers

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
153
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 59 publications
4
153
0
Order By: Relevance
“…Germ-free mice and colonization with cultured bacteria: The mice experiments were performed as a part of other published studies for understanding the strain-level differences and their role in fecal-IgA levels 7,67,68 , as well as the impact of the IBD and non-IBD microbiome on baseline immune tone and colitis. These data were used to evaluate the performance of our Strainer algorithm in defined communities of bacterial strains in germ-free mice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Germ-free mice and colonization with cultured bacteria: The mice experiments were performed as a part of other published studies for understanding the strain-level differences and their role in fecal-IgA levels 7,67,68 , as well as the impact of the IBD and non-IBD microbiome on baseline immune tone and colitis. These data were used to evaluate the performance of our Strainer algorithm in defined communities of bacterial strains in germ-free mice.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that gut microbiota strain variation impacts health [1][2][3][4][5][6][7] through mechanisms including altered immune function 8,9 and drug metabolism 10,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the potential of gut microbiota alterations to modify immune activity [14,18,37], we investigated if a defined microbiota transplant would render tumors in mN1 mice susceptible to PD-L1 blockade.…”
Section: Microbial Transplant Enhances the Effector Cd8 + T Cell Phenmentioning
confidence: 99%
“…Moreover, the bacterial taxa associated with PD-1 responding patients have varied between studies, likely owing to differences in study design and patient populations [16]. Regulation of host immunity by the microbiota often occurs at the strain level [17,18], detail not captured by 16S sequencing, which has been used to find associations between gut microbiome composition and checkpoint response in human studies [12,13,15]. five defined microbiota (mR1-mR5) responded similarly to germ-free, antibiotic, and SPF mice (figs.…”
Section: Introductionmentioning
confidence: 99%